ON BIRKHOFFS NEW THEORY OF GRAVITATION - SANDOVAL VALLARTA, MANUEL; GRAEF FERNANDEZ, CARLOS; BIRKHOFF; BARAJAS (SOCIEDAD MEXICANA DE HISTORIA NATURAL, 1946)
It is pointed out in the first place: (1) in Birkhoff's gravitational theory based on "flat" space-time, the "red shift" is accounted for by the energy change of the photon as it travels from the emitting body, whereas the photon plays no especial role in
PHYS REV D
Keywords: BIRKHOFFS, NEW, THEORY, GRAVITATION; MULTIDISCIPLINARIA; ELECTROMAGNETISMO; MAGNETISMO